An 8‐channel transceiver 7‐channel receive RF coil setup for high SNR ultrahigh‐field MRI of the shoulder at 7T. Issue 12 (28th October 2017) - Rietsch, Stefan H. G.; Pfaffenrot, Viktor; Bitz, Andreas K.; Orzada, Stephan; Brunheim, Sascha; Lazik‐Palm, Andrea; Theysohn, Jens M.; Ladd, Mark E.; Quick, Harald H.; Kraff, Oliver
Abstract : Purpose: In this work, we present an 8‐channel transceiver (Tx/Rx) 7‐channel receive (Rx) radiofrequency (RF) coil setup for 7 T ultrahigh‐field MR imaging of the shoulder. Methods: A C‐shaped 8‐channel Tx/Rx coil was combined with an anatomically close‐fitting 7‐channel Rx‐only coil. The safety and performance parameters of this coil setup were evaluated on the bench and in phantom experiments. The 7 T MR imaging performance of the shoulder RF coil setup was evaluated in in vivo measurements using a 3D DESS, a 2D PD‐weighted TSE sequence, and safety supervision based on virtual observation points. Results: Distinct SNR gain and acceleration capabilities provided by the additional 7‐channel Rx‐only coil were demonstrated in phantom and in vivo measurements. The power efficiency indicated good performance of each channel and a maximum B 1 + of 19 μT if the hardware RF power limits of the MR system were exploited. MR imaging of the shoulder was demonstrated with clinically excellent image quality and submillimeter spatial resolution. Conclusions: The presented 8‐channel transceiver 7‐channel receive RF coil setup was successfully applied for in vivo 7 T MRI of the shoulder providing a clear SNR gain vs the transceiver array without the additional receive array. Homogeneous images across the shoulder region were obtained using 8‐channel subject‐specific phase‐only RF shimming.